2009
DOI: 10.1007/s00431-009-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone maturation in extremely low birth weight infants in relation to birth weight and endocrine parameters

Abstract: Modern intensive care techniques have led to higher survival rates of extremely low birth weight infants (ELBW, birth weight <1,000 g). Previous studies have suggested a link between abnormal birth parameters and subsequent endocrine disturbances, but a possible impact on bone maturation during childhood has not been studied. ELBW children were studied (mean chronological age (CA), 6.01 years; range, 4.5-8.2). Skeletal maturation was assessed according to Greulich and Pyle (8). Bone age (BA) was defined as ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Subjects with chronic or syndromal disorders or with handicaps after severe intraventricular hemorrhages or necrotizing enterocolitis were excluded. For more details see [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with chronic or syndromal disorders or with handicaps after severe intraventricular hemorrhages or necrotizing enterocolitis were excluded. For more details see [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The original study [26] included 52 of the 178 ELBW infants born between 1999 and 2002 (29 female, 23 male, all Caucasian) at our University Children's Hospital in Bonn and enrolled there in a preterm follow-up programme. The Ethics Committee of the University Hospital in Bonn approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…There are a few reports on the factors that affect skeletal maturation in obese subjects. Adrenal androgen such as dehydroepiandrosterone sulfate (DHEAS) was positive correlated with adiposity in prepubertal children [17,18]. Sopher et al [4] reported that obesity was highly correlated with greater BA divided by chronological age (CA), and DHEAS was associated with advanced BA in prepubertal obese children and children with premature adrenarche.…”
mentioning
confidence: 99%